KONTEKSTUALISASI PEMBELAJARAN SPEAKING MELALUI KARYA-KARYA SASTRA PADA MATA KULIAH SPEAKING 3 - Aulia Nisa Khusnia (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
The research focuses on contextual speaking in teaching. It is explained teaching using literary works. The urgency of the research were based on some pitfalls from the previous class, speaking 2, such as: 1) Students understood about grammar, but they couldn’t apply it in their daily life; 2) Students couldn’t have a good conversation in everyday activities; 3) Teachers taught speaking based on topics, so that students couldn’t apply it; 4) Students had not got enough exposure yet in the classroom, so they could not have self regulated learning; 5) students got problems on their fluency in speaking. The method was used are interview and test.the aims Interview for gaining students’ problems and test for measuring students’ performance in speaking. The pictures of the research are process , dialog, performance (as a result). The result of the research is 5 ctiteria given. For comprehension and performance have very good results. For pronunciation has 78.26%, vocabulary has 69.56%, and grammar has 73.91%. Keywords: speaking contextual, speaking, literary works.